Italian account for Stephanopachys linearis (Kugelann, 1792), a species listed in Annex II of the Habitats Directive (Coleoptera: Bostrichidae) - Nardi, Gianluca; Audisio, Paolo (Fragmenta entomologica, 2016)
Three old specimens of Stephanopachys linearis (Kugelann, 1792) from NE Italy, Udine Province (Friuli-Venezia Giulia Region) are recorded. This is the first certain record of this species for Italy since the only previous records, from South Tyrol, were doubtful. This new record is of high conservation value, since this species is protected by the Habitats Directive in the European Union. Distributional and biological data on S. linearis are summarized and it is documented that the previous, doubtful literature records from South Tyrol are erroneous.